1972
DOI: 10.1103/physreva.5.1043
|View full text |Cite
|
Sign up to set email alerts
|

AtomicM-Shell Coster-Kronig, Auger, and Radiative Rates, and Fluorescence Yields for Ca-Th

Abstract: Kopfermann (Ref. 15) gives expressions for sp and pp' magnetic dipole matrix elements and sp electric quadrupole matrix elements. The latter formula, first given by Casimir IH. Casimir, Teylors Tweede Genootshap 11, 255 (1936)] is inconsistent with the matrix elements in Ref. 16, and appears to be in error. The "12" in the third term on the right-hand side of Ref. 15, Eq. (31.4), should be a "6. " We wish to thank W. J. Childs for his helpful comments and for pointing this out. The isotopic mixture of the Ne s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
1
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(97 citation statements)
references
References 10 publications
9
86
1
1
Order By: Relevance
“…The relativistic results are based on the Dirac-Fock-Slater method [58] and summed over different total angular momentum j to make a com- [53,59,60] and recommended values from various experiments and theories [61]. Bearing in mind some limitations of the nonrelativistic treatment for heavy atoms, the present results are in fair agreement with other available values.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The relativistic results are based on the Dirac-Fock-Slater method [58] and summed over different total angular momentum j to make a com- [53,59,60] and recommended values from various experiments and theories [61]. Bearing in mind some limitations of the nonrelativistic treatment for heavy atoms, the present results are in fair agreement with other available values.…”
Section: Resultssupporting
confidence: 76%
“…Thus one can expect Xe 44+ as the maximum charge state after multiphoton multiple ionization by x rays of 4500 eV, if the x-ray photon fluence is high enough to remove all n≥3 electrons via a sequence of photoionization and relaxation processes. Table I compares fluorescence, Auger, and CosterKronig rates with semi-empirical calculations [53] for Mshell single-hole configurations of Xe. Semi-empirical calculations employ transition energies from experiments, whereas the present method computes them from HFS orbital energies.…”
Section: Resultsmentioning
confidence: 99%
“…i Derived by interpolation from the widths reported for Au and Tl by Williams [60]. j Derived by interpolation from the widths ΓM4,5 and ΓN6,7 reported for Au and Bi by McGuire in [61] and [62,63] [61][62][63] are in fair agreement with our experimental values.…”
Section: Transition Widthssupporting
confidence: 81%
“…On the contrary, due to the above mentioned difficulty of theory to predict precise Coster-Kronig transition probabilities, the M 1 and to a lesser extent the L 1 and M 2,3 level widths obtained in our work are significantly overestimated by Chen et al [40,56] calculations. A comparison with the theoretical level widths reported by McGuire [61][62][63] shows the same trend for theory to overestimate the experimental results but in this case the deviations are even more pronounced. However, for the M 4,5 subshells which are not affected by Coster-Kronig transitions, McGuire's predictions are consistent with present results.…”
Section: Atomic Level Widthsmentioning
confidence: 68%
“…This author presents a complete set of the parameters in question, and moreover Auerhammer et al [10] stated that the values presented by Krause correspond better with experimental data than those of, e.g., McGuire [11] or Chen et al [12]. Problems [13]. Karttunen et al [16] found [19] and further developed by Schiebl [20] (2) According to August [24] this expression, which is similar to that presented by Ruste [25], seems to reflect the physical situation better than other quantifications found in literature.…”
Section: Introductionmentioning
confidence: 99%